Peran Aktif Ibu-Ibu dalam Pengembangan Kegiatan Keagamaan di Masjid (Studi Kasus pada Masjid Nurul Hidayah Lokasi Baru Kecamatan Air Periukan) - Nur Safitri, Azizah; Melati, Cahaya; Inda Anggraini, Lici; Tri Listri, Indah; Wali Yullah, Fadhil; Saepudin, Saepudin (MENYALA: Jurnal Pengabdian Masyarakat, 2024)
This study aims to identify and analyze the role of mothers in planning, implementing, and supporting religious activities at Nurul Hidayah Mosque. This research also explores the challenges faced by mothers in actively participating. Methods This research uses qualitative methods with data collection techniques through in-depth interviews, participatory observation, and document analysis. Data was collected from various sources, including mosque administrators, mothers involved in activities, and community members. The results showed that mothers play an important role in various aspects of religious activities at Nurul Hidayah Mosque. They are actively involved in organizing events, religious education, social programs, and charity activities. Mothers also contribute in supporting and motivating family and community participation. However, they face significant challenges related to time-sharing between household responsibilities and involvement in the mosque, as well as social perceptions that limit their role in decision-making.